Síntese, caracterização e estudo de atividade biológica de complexos de prata(I) contendo ligantes baseados na 1,10-fenantrolina e tiouréia - Segura, Daniel Fonseca [UNESP] (2014)
Even Ag0, and its derivates, being not an essential element, they have presented medicinal applications such as water purification, injuries treatment, antiinfection recovery of medical instruments, burn treatment as they have powerful antimicrobial properties and low human toxicity. Silver compounds have been used as antimicrobial agent since the beginning of human history when it was added to potable water for preservation as a primary resource in military conflicts. In the present work novel silver complexes (I) of Ag(NN)(tu)X type in which X = 2,2-bipiridine (bpy), 1,10-phenantroline (phen), dipirido[3,2-a:2’,3’-c]phenazine (dppz) and 1,10- phenantroline-5,6-dione (phd); tu= thiourea and X=NO3 -, CF3SO3 -, BF4 - and SO4 2- have been synthesized and characterized. The complexes had been characterised by infrared spectroscopy, 1H nuclear magnetic resonance, elementary analysis and mass spectroscopy techniques. The crystal structures of [{Ag(bpy)(μ- tu)}2](NO3)2 (A1) and [{Ag(phd)(μ-tu)(tu)}2](CF3SO3)2 (D2) were determined by single crystal X-ray diffraction indicating a binuclear system with silver(I) centers bridgebonded by sulphur atoms of thiourea molecule. The in vitro biological activity of [Ag2(bpy)2(tu)2](NO3)2 (A1), [Ag2(phen)2(tu)2](NO3)2 (B1) e [Ag2(phen)2(tu)2](CF3SO3)2 (B2) compounds had been studied for fungi (C. albicans, C. tropicalis e C. krusei), bacteria (S. aureus, E. coli e P. aureginosa), M. tuberculosis and amastigote and promastigote forms of L. amazonensis. Although a reduced study has been performed in view of the microorganisms and compounds quantities it was possible to evaluate some changes on biological behavior by both chelant ligand NN and counterion modification. Promising results were obtained on the antileishmanial activity for B2 compound which have showed a selectivity index (SI) of 13,8-15,5 values much higher than the observed for AmpB, the standard drug (5,5-5,83).